(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2024)
A manufacturing company should use its resources (i.e., manpower, machinery, and so on) in an efficient manner to improve productivity and minimize cost. The purpose of the present study was to recommend improvement methodologies for production in a company that designed a cutting tool to be installed on the bottom of a boring machine. To produce the cutting tool, the company has used traditional technology that has resulted in a lengthy processing time and a delay in supplying the finished goods to the vendors. This article 1) described how the process was adopted by the organization.